Development Of The World Halal Industry Halal Guarantee System In Its Development In Some Countries - Ri Esso*, Andi Sawe; Ismail, Ismail; Lutfi, Mukhtar (Universitas Syiah Kuala, 2024)
This article discusses the development of halal guarantee systems in several countries and its implications for the global food and beverage industry. With increasing consumer awareness of halal products, demand for halal products continues to increase significantly. Therefore, countries that have large Muslim populations or significant export markets to Muslim-majority countries have developed comprehensive halal assurance systems. This article examines some of the approaches taken by countries such as Malaysia, Indonesia, Turkey and the United Arab Emirates in building and managing their halal assurance systems. Apart from that, the economic, social and political implications of this halal guarantee system are also discussed. Through this analysis, this article provides insight into how the halal guarantee system plays a role in driving the growth of the food and beverage industry in an increasingly developing global market.